1993
DOI: 10.1177/107049659300200107
|View full text |Cite
|
Sign up to set email alerts
|

Trade Policy and Industrial Pollution in Latin America: Where Are the Pollution Havens?

Abstract: It is commonly assumed by economists and environmentalists alike that greater economtc "openness" will lead to increased industrial pollution in developing countries. This paper challenges the "pollution haven" hypothesis, arguing that liberalization of trade regimes and increased foreign investment in Latin America have not been associated with pollution-intensive industrial development. From case studies and econometric evidence, we conclude that protected economies are more likely to favor pollution intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
270
4
25

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 538 publications
(315 citation statements)
references
References 0 publications
16
270
4
25
Order By: Relevance
“…In their classical study, Grossman and Krueger (1993) …nd no evidence to suggest that higher pollution abatement costs in the US had a signi…cant impact on imports from Mexico or from maquiladora sectors in particular. Birdsall and Wheeler (1993) …nd similar results in their study of Latin America, arguing that closed economies are more likely to favor pollution intensive industries, while openness actually encourages cleaner industry through the importation of developed-country pollution standards. In contrast, Low and Yeats (1992) do …nd some evidence of an association between the rise in environmental control costs in developed countries and the creation of pollution havens in poor countries.…”
Section: Motivation and Literature Reviewsupporting
confidence: 62%
“…In their classical study, Grossman and Krueger (1993) …nd no evidence to suggest that higher pollution abatement costs in the US had a signi…cant impact on imports from Mexico or from maquiladora sectors in particular. Birdsall and Wheeler (1993) …nd similar results in their study of Latin America, arguing that closed economies are more likely to favor pollution intensive industries, while openness actually encourages cleaner industry through the importation of developed-country pollution standards. In contrast, Low and Yeats (1992) do …nd some evidence of an association between the rise in environmental control costs in developed countries and the creation of pollution havens in poor countries.…”
Section: Motivation and Literature Reviewsupporting
confidence: 62%
“…These include low gradual dependence on natural resources, increasing importance of government sector in the economy, and an increase in the importance of formal education reflected in the economy.  Birdsall and Wheeler [4], Lee and Ronal-Holst [5], and Jones and Rodolfo [6] all have indicated that in theory, foreign trade has an effect on economic expansion proportionate to expansion in production(especially industrial) as a result of external demands for products and services; that is, these economic activities have a direct impact on pollution. Foreign trade also results in decomposition, which must be understood as the decline of the great centers of world production due to migration to other countries with comparative advantages over the country of origin; this serves to increase the foreign trade between countries, but also spreads and increas-es pollution, known as the "Pollution Haven Hypothesis".…”
Section: Economic Growthmentioning
confidence: 99%
“…For example, Birdsall and Wheeler (1993), drawing on case studies and econometric evidence, claim that increased foreign investment in Latin America has not led to an increase in pollution-intensive industrialization (see also Walter 1978). Similarly, Wheeler (2001) comparing data for trends in air quality in the United States versus China, Brazil and Mexico (then the largest recipients of foreign investment in the developing world) found that air quality had actually improved from the 1980s through the mid-1990s in all four countries (see also Mani and Wheeler 1998).…”
Section: The Pollution Haven Hypothesismentioning
confidence: 99%